Prediction for debonding damage process of glass beads-reinforced modified polyphenylene oxide under simple shear - Tsui, C.P.; Chen, D.Z.; Tang, C.Y.; Uskokovic, P.S.; Fan, J.P. (Journal of materials processing technology, 2005)
A three-dimensional finite element cell modeling technique has been applied to predict the particle–matrix debonding process of particulate polymer composite (PPC) subject to simple shear loading. The particle–matrix debonding in PPC has been simulated by using two different debonding criteria: stress-based and strain-based. The stress-based debonding criterion uses the hydrostatic tensile stress as a critical stress while the strain-based one uses the equivalent plastic strain at failure as a critical factor for element failure. In this analysis, glass beads-reinforced polyphenylene oxide (GB/PPO) has been used for verification of the predicted results. As compared with the results from scanning electron microscopy (SEM) based in situ simple shear test of GB/PPO composite, the model with the stress-based criterion is much more appropriate for simulation of the shear damage process. The importance of selecting an appropriate debonding criterion for achieving correct simulation results could be revealed. The essential information like the threshold strain for initiation of shear damage could then be acquired from the model with the verified stress-based debonding criterion.